PEMIDANAAN PELAKU TINDAK PIDANA PERSETUBUHAN DAN PENCABULAN PADA ANAK (PUTUSAN NOMOR 429/PID.SUS/2021/PN.BDG): Crimination Of Persons Of Criminal Actions And Abuse Of Children (Decision Number 429/Pid.Sus/2021/PN.Bdg) - Rahul, Muhammad; Multiwijaya, Vientje Ratna (Faculty of Law, Universitas Trisakti, 2024)
Punishment of the perpetrators of the crime of intercourse and obscenity against children is imposed by the judge with sanctions on the perpetrators who commit intercourse and obscenity of minors on the basis of article 81 paragraph 1 jo 76 D of Law no. 17 of 2016 concerning the stipulation of the government in lieu of law number 1 of 2016 regarding the second amendment to law number 23 of 2002 concerning child protection into law. With Study Decision Number 429/Pid.Sus/2021/PN.Bdg. In this decision there were things that were contrary to the facts. The main issues are 1) How is the punishment of perpetrators of sexual intercourse and sexual abuse of children appropriate or not based on Article 81 paragraph 1 in conjunction with Article 76 D of Law no. 17 of 2016 (Decision Number 429/Pid.Sus/2021/PN. Bdg)? and 2) Can the actions of the perpetrators of the crime of intercourse and sexual abuse of children be categorized or not as a combined crime (Decision Number 429/Pid.Sus/2021/PN. Bdg)?. This study uses a normative type that is descriptive analysis, uses secondary data obtained from literature studies, and the data is processed qualitatively by drawing deductive logical conclusions. Conclusion 1) the punishment of the perpetrators of the crime of sexual intercourse is inappropriate based on Article 81 paragraph (1) in conjunction with Article 76D of Law No. 17 of 2016, and 2) The actions of the perpetrators of the crime of sexual intercourse and sexual abuse of children are included in the combined category of criminal acts.